Who is at risk of occupational Q fever: new insights from a multi-profession cross-sectional study. Issue 2 (9th February 2020) - Groten, Tanja; Kuenzer, Karola; Moog, Udo; Hermann, Beate; Maier, Katrin; Boden, Katharina
Abstract : Objectives: Q fever is a zoonosis caused by the bacterium Coxiella burnetii . It is recognised as an occupational hazard for individuals who are in regular contact with animal birth products. Data from the literature are not comparable because different serological assays perform very differently in detecting past infections. It is therefore essential to choose the right assay for obtaining reliable data of seroprevalence. Obstetricians are another profession potentially at risk of Q fever. They can be infected from birth products of women with Q fever during pregnancy. There is little data, however, for Q fever in this occupational group. Our study therefore had two purposes. The first was to obtain reliable seroprevalence data for occupational groups in regular contact with animal birth products by using an assay with proven excellent sensitivity and specificity for detecting past infections. The second purpose was to obtain primary data for obstetricians. Design: We carried out a cross-sectional study. Setting: The study included shepherds, cattle farmers, veterinarians and obstetricians from Thuringia. Participants: 77 shepherds, 74 veterinarians, 14 cattle farmers, 17 office employees and 68 obstetricians participated. The control group consisted of 92 blood donors. Primary outcome measure: The primary outcome measure was C. burnetii phase II specific IgG. The assay used was evaluated for this purpose in a previous study. Results: Of the 250 blood samples we analysed, the very highest seroprevalences (64%–77%) occurred in individuals with frequent animal contact. There were no significant differences between shepherds, cattle farmers and veterinarians. The seroprevalence in people working in administration was lower but still significantly greater than the control. No obstetricians or midwives tested positive. Conclusions: Shepherds, cattle farmers and veterinarians have a high risk of C. burnetii infection. However, our study clearly proves that there was no increased risk for people working in an obstetric department.